Penerapan Metode Always Better Control (ABC) Terhadap Pengendalian Persediaan Bahan Baku Perishable Olahan Hasil Laut Pada UD.XYZ - Alfin Nur Syifa', Muhammad; Novi Marlyana; Spalanzani, Widya (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
UD. XYZ is a trading business engaged in the processing and distribution of seafood, facing challenges in managing raw material inventory due to seasonal fluctuations and supply uncertainties. A lack of attention to raw material availability, especially perishable items such as fish, shrimp, and squid, poses a risk of quality deterioration and financial losses is not properly managed. The classification of raw materials based on their importance and contribution helps improve operational efficiency. By applying the Always Better Control (ABC) method, The company can manage inventory more optimally and reduce costs. The analysis results show that category A with a cumulative percentage 1-85% includes key raw materials such as milkfish, shrimp, squid, and wader fish. Category B with a cumulative percentage 86-95% consists of cooking oil, garlic, shallots, and eggs. Category C with a cumulative percentage 96-100% includes wheat flour, rice flour, ginger, candlenut, tapioca flour, salt, cornstarch, turmeric, bay leaves, lime juice, stock powder, coriander, and pepper